Memory metal stents for palliation of malignant obstruction of the oesophagus and cardia. Issue 3 (September 1995) - May, A; Selmaier, M; Hochberger, J; Gossner, L; Mühldorfer, S; Hahn, E G; Ell, C
Abstract : Thirty patients with incurable malignant obstruction of the oesophagus and cardia were treated with self expanding oesophageal memory metal stents (Ultraflex) in a prospective study. The endoprostheses were successfully placed in all patients. Within one week after implantation dysphagia had improved in 25 of 30 patients (83%). Stent expansion was incomplete within one week after implantation in 12 of 30 patients (40%). After an average of two dilatation sessions eight of 12 stents had expanded completely. Five patients complained of retrosternal pain and three of them suffered from heartburn over several days despite acid inhibition. Major problems in the follow up period occurred in 10 of 30 patients (30%) and included late perforation (one) and tumour ingrowth/overgrowth (nine). All of these complications were treated endoscopically. Improvement of the dysphagia of the patients with tumour ingrowth/overgrowth lasted for about eight weeks (median; range: 2-38 weeks). Until November 1994 six of 30 patients were still alive with a survival time of 309 days (median; range: 103-368 days). It is concluded that oesophageal memory metal stents are easy to implant, prove effective in the palliation of malignant oesophageal obstructions, and have a low risk of severe complications. The only disadvantages are that incomplete initial stent expansion as well as tumour ingrowth/overgrowth occurred in nearly one third of the patients.